Implementation of Tourism Village Policy Based on The Collaborative Governance Plus Multi-Helix (CGPMH) Model in Pujon Kidul Tourism Village, Malang Regency - Fitriana, Annisa Nur; Wijaya, Andy Fefta; Wanto, Alfi Haris (Universitas Sultan Ageng Tirtayasa, 2024)
The successful development of the national tourism sector is the result of positive trends at the regional level, including East Java Province. As stipulated in Law No. 6/2014, the government grants special rights and authorities to villages, referred to as village autonomy. This research examines the implementation of the tourism village policy in Pujon Kidul Tourism Village, Malang Regency, which has been developing for 10 years. After the COVID-19 pandemic, the number of tourists and PAD decreased, so a marketing strategy and revitalization of tourism potential were needed. This research uses Grindle's (1980) framework and Collaborative Governance Plus Multi-Helix. A qualitative-descriptive approach was used by the researcher to find primary and secondary data. The results show that the tourism village policy has run as expected with alignment between implementers and target groups, without resistance. In addition, policy implementation is participatory with the support of internal and external resources. However, it is still necessary to increase the level of community compliance to maximize the benefits of the policy, as well as adaptive strategies to maintain the sustainability of tourism in Pujon Kidul.